Civil Law Analysis of Misbruik Van Omstandigheden in Hospital Refusal of Economically Weak Patients - Yusriando, Yusriando; Gunarto, Gunarto; Suseno, Jarot Jati Bagus; Yuliati, Sri (Jurnal Pembaharuan Hukum, 2025)
Hospitals in Indonesia, as mandated by the 1945 Constitution and health law policies, are required to provide equitable healthcare services to all citizens, including economically disadvantaged groups. However, frequent cases of hospital rejections against poor patients due to inability to pay reveal a gap between constitutional guarantees and practice. Such acts constitute misbruik van omstandigheden (abuse of circumstances), where hospitals exploit patients' positions vulnerable in therapeutic agreements and informed consent. The objectives of this research are threefold: first, to analyze the practice of misbruik van omstandigheden in medical contracts between hospitals and poor patients; second, to assess the form of legal responsibility of hospitals in cases of denial or neglect, and third, to formulate recommendations to strengthen the protection of poor patients' rights through regulatory reforms and effective sanctions. This study employs a doctrinal research method with a normative legal approach, supported by empirical case studies. Primary sources include the 1945 Constitution, Law Number 36/2009, Law Number 17/2023, and the Civil Code, complemented by Islamic legal principles (maqashid al-Shariah). The findings show that hospital rejections violate civil law, constitutional mandates, and ethical obligations.